Microbiological quality determination of pasteurized, UHT and flavoured milk sold in Dhaka, Bangladesh (Stamford Journal of Microbiology, 2019)
The present study was undertaken to determine the microbiological quality of pasteurized milk, UHT milk and flavoured milk samples collected from different locations in Dhaka, Bangladesh. Twenty pasteurized milk samples, fifteen UHT milk samples and fifteen flavoured milk samples of different brand were collected and different batch were analyzed for enumerating the total viable bacterial count (TVBC), total coliform count (TCC) and physiochemical tests (sensory test, alcohol test, acidity test, fat test, CLR test, SNF). The range of TVBC and pasteurized milk samples was between 2.3×102 cfu/ml to 4.69×103 cfu/ml. TVBC range of flavoured milk samples was between 5.0×101 cfu/ml to 1.8×102 and no TVBC was detected for any of the UHT milk samples. No TVBC was found for flavoured milk samples of company-8 (UHT). Because it was processed with ultra high temperature, slightly lower than that recommended by BSTI (not exceeding 20,000 cfu/ml). Coliform bacteria were present only for pasteurized milk samples in one brand, though the count was under acceptable range according to BSTI recommendation (